Comparative evaluation of propofol and ketamine total intravenous anaesthesia (TIVA) with dexmedetomidine and butorphanol in goats - KUMAR, ROHIT; KINJAVDEKAR, P; AMARPAL, AMARPAL; AITHAL, H P; PAWDE, A M; SINGH, J; KHATTRI, S (The Indian Journal of Animal Sciences, 2018)
The present study was aimed to compare clinicophysiological, and haemodynamic effects of propofol and ketamine anaesthesia with dexmedetomidine-butorphanol premedication. Prospective, randomized clinical trial, with owner consent was performed on sixteen clinical cases of urolithiasis in goats. After sedation with dexmedetomidine (2.5 μg/kg body wt) and butorphanol (0.05 mg/kg body wt), anaesthesia was induced and maintained with either propofol or ketamine. For maintenance, continuous intravenous infusion (CII) at variable rate was used with respective drug. Infusion rate was adjusted in response to positive reactions to surgical nociceptive stimulation performed during tube cystostomy procedure. Clinicophysiological, and haemodynamic parameters were measured before treatment (baseline), after sedation and during anaesthesia. One way repeated measure analysis was used to compare the mean values at different intervals in each group for non-parametric observations. Mann whitney U test was used to compare median score between groups at corresponding intervals. Compared to baseline, HR (heart rate) improved at 15 min and onwards but remained significantly (P=0.030) lower than the baseline value in both groups. MAP (mean arterial pressure) decreased significantly (P=0.022) up to the end of the observation period in DBP (dexmedetomidine + butorphanol+ propofol); however, in DBK (dexmedetomidine + butorphanol + ketamine) improvement in MAP was observed at 15 min and onwards with significantly (P=0.018) lower values at 15 and 20 min and a non-significantly (P=0.080) lower value at 30 min as compared to the baseline value. Both drug combinations are suitable to induce and maintain anaesthesia for one hour, with good haemodynamic stability and analgesia. However, DBP is related with excellent sedation and muscle relaxation.